APPLICATIONS OF EPIGENETICS IN FORENSIC INVESTIGATIONS: A BRIEF REVIEW - Ullah, RA; Ali, A; Hussain, N; Malik, A (Biological and Clinical Sciences Research Journal, 2021)
Forensic science is a discipline that has the capacity to be merged with every promise to offer a solution to a criminal investigation to help the legal system. Epigenetics is a branch of genetics that deals with the study of environmental interaction with the genome. The emerging field of forensic epigenetics has a variety of applications in criminal investigations. It provides an addictive tool to solve criminal activity-related issues. In this review, we have showcased the brief use of epigenetics to sort out forensic-related issues and help the legal system. We have briefly taken a snapshot of genetics, epigenetics, and application of epigenetics in forensic science that how it could offer solutions to queries of forensic nature. Also, potential future developments in the field and their probable impact have been anticipated. It has many potential applications which are still to be explored. It complements forensic science at many potential levels.